Testing (CSOL) and various types of test takers - Jelaska, Zrinka; Cvikić, Lidija (2009)
After showing differences between testing speakers vs. learners, this paper discusses speakers of different L1, esp. closely related languages. It also discusses a few other types of test takers pointing to the problems in testing knowledge of language with respect to test takers social status, cognitive status, education and age. The objective is to raise awareness of different test takers, e.g. the problem of testing people regardless of their characteristics.
Projekt MZOS
ENG